Living electrodes based on green algae in hydrogels. Issue 4 (2nd February 2021) - Al-Mossawi, Mohammed; Warren, Holly; Molino, Paul J.; Calvert, Paul; in het Panhuis, Marc
Abstract : We report living electrode materials from green algae " Chlorella vulgaris " embedded within alginate hydrogel and cross-linked at different calcium chloride concentrations. Abstract : Soft and living electrodes offer new possibilities for addressing the biological–electrical interface beyond the use of traditional metal based bio-electrodes. Here, we present a living electrode material from green algae " Chlorella vulgaris " embedded within alginate hydrogel and cross-linked at different calcium chloride concentrations. Mechanical, rheological, electrical and biological properties of the living electrode materials were assessed to investigate the impact of algal growth on the characteristics of resulting gels. The electrical behaviour of the algae/alginate hydrogels was characterised using electrical impedance spectroscopy. Living electrodes containing algae exhibit conductivity values of up to 4.9 ± 0.2 mS cm −1 . These conductivity values were sufficient to use these living hydrogels as electrode components in simple electrical circuits.